Nivel de conocimientos financieros de los microempresarios del distrito de Punchana, periodo 2021 - Dávila Rengifo, Christian (2022)
The present research work entitled "Level of Financial Knowledge of the Microentrepreneurs of the District of Punchana, Period 2021" was carried out with the objective of determining the level of Financial Knowledge of the Microentrepreneurs of the District of Punchana, period 2021, for this it was used the type of descriptive research and the design of the research was Non-Experimental, 40 Microentrepreneurs from the District of Punchana were taken into account as a study population, to whom a survey was applied with the data collection instrument called a questionnaire; The work concluded that the level of Financial Knowledge of the Microentrepreneurs of the District of Punchana, period 2021 is Medium.